Extra Calot’s Subserosal Gallbladder Dissection without Clipping of Cystic Artery is a Safe Technique of Laparoscopic Cholecystectomy for Acute Cholecystitis - Muhammad Zulfiqar Ali (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Laparoscopic cholecystectomy remains the gold standard for treating gallbladder disease but carries a risk of bile duct injury, especially in cases of acute cholecystitis with distorted anatomy. This study evaluated the safety and effectiveness of an extra-Calot’s subserosal dissection technique without clipping the cystic artery, aiming to minimize complications. Materials and Methods: This cross-sectional observational study was conducted at Alhada Armed Forces Hospital and Prince Mansoor Military Hospital over 18 months. A total of 98 patients with clinically and radiologically confirmed acute cholecystitis underwent emergency laparoscopic cholecystectomy using the described technique. Patients with obstructive jaundice, malignancy, or choledocholithiasis were excluded. Data on demographics, surgical outcomes, laboratory values, and complications were recorded and analyzed using SPSS version 26. Results: Among 98 evaluated patients, the majority were female (58.2%), with a mean surgery duration of 116.73 ± 51.9 min. No major intraoperative or post-operative bleeding, bowel injury, or transfusion was recorded. One patient had a transient biliary leak through the drain and no patient had bile duct injury. Logistic regression identified gallbladder wall thickening >4 mm as a significant predictor of bile duct injury (odds ratio = 6.10; P = 0.034). No significant changes were noted in hemoglobin or liver enzymes postoperatively, except for reductions in albumin and total protein levels (P < 0.001). Conclusion: The extra-Calot’s subserosal dissection technique without cystic artery clipping appears to be a safe and effective method for managing acute cholecystitis, minimizing critical complications. Further studies with larger cohorts are warranted to validate its widespread applicability.